Impact of bedding material on behavioural pattern of Osmanabadi goat kids - KASHYAP, K; PATHAK, R; SANTRA, A K; SINGH, N; MISHRA, O P; PARMAR, M S; DONERIA, R; KASYAP, S (The Indian Journal of Animal Sciences, 2024)
Bedding materials play significant role to provide comfortable microenvironment to animals under intensive production system, which can be assessed by behaviour of the animal. The present study observed the effect of bedding material in different behaviour parameters of Osmanabadi goat kids. A total number of 18 Osmanabadi goat kids between 2-3 months of age were distributed into three groups (6 kids per group): control (T0) and treatments (T1, T2). The kids in T0 were reared in concrete floor without any bedding material, whereas treatment groups T1 and T2 were composed of wood shavings and straw bedding material, respectively. At the end of experiment lying time per day of T2 group was significantly higher as compared to T0 and T1 groups. Lying time per bout was significantly higher in T2 group than T0 group, but corresponding values were similar to that of T1 group. Standing time per day was higher in concrete floor (T0) as compared to wood shavings and straw bedding group. Fighting behaviour was significantly higher in kids kept in concrete floor and wood shavings group than those kept in straw bedding group. Grooming behaviour was higher in T2 group as compared to T0, but similar to T1 group and kids had more negative behaviour in concrete floor. Overall, it can be concluded that straw bedding has a positive influence on the welfare of growing kids and therefore can be used as an alternative bedding material in growing goat kids.